A Review of Preconcentrator Materials, Flow Regimes and Detection Technologies for Gas Adsorption and Sensing. Issue 20 (12th June 2022) - Chowdhury, Aminur Rashid; Lee, Tse‐Ang; Day, Coco; Hutter, Tanya
Abstract: A preconcentrator is a device used to lower the detection limit of a gas sensor, often integrated upstream of the sensor. Gas preconcentrators have attracted great research interest because of their wide range applications including atmospheric pollution detection, breath analysis, and homeland security. Nanoporous materials, such as carbonaceous adsorbents, metal‐organic frameworks, metallic adsorbents, and oxides, are used to preconcentrate gases for improving detection capability. In this review, preconcentrator materials, detection technologies, and integration with detector configurations are surveyed. Current limitations and future improvement opportunities are also discussed. Abstract : Gas preconcentrators are used to lower the detection limit of gas sensors. This is achieved by analyte adsorption in a porous preconcentrator material, followed by a quick desorption, consequently increasing analyte concentration in the outlet of the preconcentrator. This review describes progress in gas preconcentrators focusing on preconcentrator materials and flow configurations.